Analisis Unsur Intrinsik dan Ekstrinsik Novel Laskar Pelangi Karya Andrea Hirata - Tiara Zalma Prasiska; Yesi Novita Wulandari; Novita Indriyani; Abdurahman . (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This study analyzes the intrinsic and extrinsic elements in the novel Laskar Pelangi by Andrea Hirata. The main issue addressed in this study is how the intrinsic and extrinsic elements are interconnected and how they contribute to constructing the overall meaning of the literary work. The objective of this study is to describe and interpret the relationship between these elements in order to reveal the deeper meaning and educational values embedded in the novel. This study employs a qualitative descriptive approach using content analysis techniques. The data were collected through intensive reading, identification, and systematic classification of textual elements related to intrinsic and extrinsic aspects. The analysis focuses on structural elements such as theme, characters, plot, setting, and point of view, as well as external aspects including social, cultural, moral, and religious values. The results show that the intrinsic elements are systematically interconnected and form a coherent narrative structure that supports the development of the story. Meanwhile, the extrinsic elements reflect the real conditions of society and strengthen the messages conveyed by the author. The study also reveals that the novel functions not only as a source of entertainment but also as a medium of education and social reflection. Therefore, the integration of intrinsic and extrinsic elements significantly contributes to the depth, meaning, and relevance of the literary work for readers.